2013
DOI: 10.1139/bcb-2012-0044
|View full text |Cite
|
Sign up to set email alerts
|

The epigenetic potentials of dietary polyphenols in prostate cancer management

Abstract: Prostate cancer is a disease that is greatly affected by lifestyle, particularly diet, and is more prevalent in US and European countries compared with South and East Asia. Among several known causes and risk factors, nutrition plays an important role in prostate cancer pathogenesis. Various dietary components including polyphenols have been shown to possess anticancer properties. Dietary polyphenols have been the subject of extensive studies for the last decade because of their anticancer and chemopreventive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Prostate cancer (PCa) is the second most common cause of cancer-related death in men in the USA because of advanced castrate-resistant disease and associated metastasis. Since the incidence of this slow growing cancer is very high and diet is an associated risk factor [1], efforts have been driven toward the development of chemopreventive strategies with the use of natural bioactive compounds [2][3][4]. Our group has shown that stilbenes, particularly resveratrol and pterostilbene found in grapes and blueberries, have targeted chemo-protective effects against PCa in vitro and in vivo [5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer (PCa) is the second most common cause of cancer-related death in men in the USA because of advanced castrate-resistant disease and associated metastasis. Since the incidence of this slow growing cancer is very high and diet is an associated risk factor [1], efforts have been driven toward the development of chemopreventive strategies with the use of natural bioactive compounds [2][3][4]. Our group has shown that stilbenes, particularly resveratrol and pterostilbene found in grapes and blueberries, have targeted chemo-protective effects against PCa in vitro and in vivo [5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Lifestyle factors, such as diet and nutrition, play a significant role in the pathogenesis of PCa, and multiple studies have revealed that intensive nutrition and lifestyle changes might modulate gene expression in the prostate. These findings highlight the potential role of dietary phytochemicals in the treatment of PCa[35]. Studies evaluating epigenetic modifications in cancer, specifically those that lead to the inactivation or silencing of key regulatory genes, such as tumor suppressor genes, has led to the realization that genetic and epigenetic changes play a critical role in tumorigenesis[6].…”
Section: Introductionmentioning
confidence: 99%
“…The tea plant (Camellia sinensis) has been cultivated in Asia for thousands of years and green tea has been used for centuries in China, Japan, and Thailand as a traditional medicine with a variety of applications (Abbas et al 2013). Over the last two decades, many epidemiological studies have evaluated the chemopreventive properties of green tea, suggesting that increasing intake of green tea is correlated with significant decrease in the development of prostate cancer.…”
Section: Epigallocatechin-3-gallatementioning
confidence: 99%